Activity Of Charity and Civil Society Organizations in Gaza - Hamarsha, Manal Mohammed Yousef (Civil Szemle, 2025)
Many charitable and civil society organizations have made tremendous and extensive efforts during the crisis in Gaza, playing a crucial role in addressing the urgent and critical needs in the region. Despite their inability to meet all humanitarian needs and requirements due to the restrictions imposed on them under current circumstances and war conditions, they have played a significant role and initiated numerous activities in a substantial manner. Non-profit organizations must highlight this role. This article provides a comprehensive theoretical description of the activities of various organizations, including the Reconstruction Alliance, the World Food Programme, the Women’s Program Center in Rafah, ActionAid, USAID, Islamic Relief, and UNRWA. Through this study, we will highlight the efforts of these multifaceted institutions to mitigate and alleviate the crisis, supporting the people of Gaza and emphasizing the importance of both immediate relief and long-term recovery initiatives. This research paper will provide qualitative evidence. Interviews were conducted with staff members of these seven organizations to provide a comprehensive picture. The scale of these organizations' activities and initiatives during the crisis provides a clear understanding of the collaborative and individual efforts between them.In conclusion, this study highlights the crucial role of diverse organizational efforts in addressing the humanitarian crisis in Gaza. The specific focus of each organization, along with coordinated efforts, played a vital role in addressing the complex needs of the affected population. The findings provide valuable insights into the effectiveness of these responses and offer recommendations for strengthening future humanitarian strategies in similar crises.